School Climate Questionnaire: A New Tool for Assessing the School Environment - Alexandra A. Bochaver; Aleksei A. Korneev; Kirill D. Khlomov (Frontiers in Psychology, 2022)
The school environment is of great importance for the socialization of children. At school, children learn many values, rules, and skills that relate to building relationships that include friendship, support, and competition. The school largely shapes children's behavior and expectations from society in the future. This study validates the new 22-item School Climate Questionnaire (SCQ) using a sample of Russian school students. A total of 4,776 respondents from 9 to 18 years old participated in the correlational study and filled the online-survey that includes SCQ. The Revised Olweus Bully/Victim Questionnaire, the Warwick–Edinburgh Mental Well-Being Scale (WEMWBS), and the Academic Motivation Scale were used to examine the convergent validity of the SCQ. Two hypotheses were examined that the new tool SCQ has structural validity (three factors) and convergent validity (which is proven by the significant correlations with victimization, aggression, mental wellbeing, and academic motivation). According to confirmatory factor analysis (CFA), it was shown that the questionnaire has three factors; their reliability is satisfactory. As expected, the results revealed significant correlations between the three scales of SCQ and scales of Victimization, Aggression, Mental Well-Being, and different types of Academic Motivation. The SCQ is a reliable and valid instrument that may be recommended for use by researchers and practitioners in different areas of educational psychology.